Non-timber forest products and environmental valuation of the National Forest Pacotuba, ES - Silva, Eth Rocha; Mendonça, Adriano Ribeiro; Fernandes, Milton Marques; Dias, Henrique Machado; Silva, Mayra Luiza Marques da (Revista de Ciências Agroveterinárias, 2019)
This study aimed to evaluate the potential for the extraction of non-timber forest products (NTFPs) and environmental valuation by the willingness to receive from the residents of the damping zone of the National Forest (FLONA) of Pacotuba, state of Espírito Santo. Forms were applied in a sample of 78 families, in the community of Monte Alegre, located in the damping zone of the FLONA de Pacotuba, for the NTFPs ethnobotanical survey and the willingness to receive to maintain the forest cover. The mapping use of the soil Pacotuba FLONA and the damping zone were obtained through a Landsat image. The contingent valuation method was used using the forms to estimate the willingness to receive to maintain the forest cover. At FLONA de Pacotuba there is potential to produce NTFPs, with an offer mainly for medicinal and ecological purposes. The use of the soil demonstrates that the FLONA of Pacotuba presents a high percentage of forest cover, however the damping zone is with a high percentage of pasture and use of the soil Anthropic, with the payment for environmental services (PES) an alternative to increase the forest cover in the cushioning zone. The willingness to receive to maintain the forest cover of the owners in the damping zone and in the FLONA was greater than the PES of the state of Espírito Santo, which hinders the adoption of a payment program for environmental services. The PES of Espírito Santo, through the program Reflorestar, associated with the management of NTFPs, mainly medicinal and ecological, would be alternatives for income generation and preservation of the forest cover.